Corruption and FDI: The role of social brokers - Jose Godinez; Mahmoud Khalik (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
To reduce engagement in corruption, firms are increasingly accountable for the behavior of their intermediaries. However, current anti-corruption efforts have not included those agents that arrange the initial meetings between foreign MNEs and potential local partners. We call these initial intermediaries "social brokers." In our Perspective piece we argue that "social brokers" should be included in anti-corruption efforts.
Keywords: 330